THE EFFECT OF REMOTE ISCHEMIC PRECONDITIONING IN DIABETIC PATIENTS AFTER ELECTIVE PERCUTANEUS CORONARY INTERVENTION - ANGGRIYANI, NOVI; PARAMITA, DONNA; RIFQI, SODIQUR (JNH (Journal of Nutrition and Health), 2015)
Background Experimental and clinical investigations suggest that reperfusion is considered ?a double-edged sword?, as reperfusion would restore oxygen and nutrients supply to the ischemic myocardium to improve its functional recovery, but in the other hand reperfusion could augment myocardial ischemic damage, known as myocardial ischemia-reperfusion (I/R) injury. The brief and repeated cycles of I/R given at a distant organ before a sustained ischemia and reperfusion, known as remote ischemic preconditioning (RIPC), would protect the heart from lethal I/R injury. Objective The effect of ischemic preconditioning in a diabetic heart is a contradictory whether it could improve or worsen the damage degree of myocardial  I/R injury, as reported by some previous studies. These inconsistent reports need further studies. Methods Twenty-four diabetic patients with stable CAD undergoing elective percutaneus coronary intervention were randomly assigned to 2 groups: 14 patients submitted to RIPC and 10 patients were control group. We induced RIPC by inflating a blood pressure cuff placed on the upper limb to 20 mmHg above systolic arterial pressure for 5 min and deflating the cuff for 5 min; 4 cycles were performed. All patients had CK-MB level measured at baseline and 18-24 hours after the elective PCI. Myocardial injury was considered when post-PCI CK-MB level rose up to 1-3 fold of the upper normal limit. Results A higher proportion in control group (40%) experienced myocardial injury, compared with the group receiving RIPC (0%) (p = 0.02). The mean of baseline CK-MB was equal in both control and RIPC groups (19.07 ± 2.84 and 17.5 ± 2.32, respectively; p = 0.165). While the mean of post-PCI CK-MB level in two groups differed significantly (34.2 ± 10.43 and 24.42 ± 4.03, respectively; p = 0.017). Conclusions RIPC lower the incidence of myocardial injury in diabetic patients after elective percutaneus coronary intervention. These data suggest that diabetic patients still gain protection of RIPC.